2008
DOI: 10.1126/science.1159846
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interstitial Sites in the Ti 3d Defect State in the Band Gap of Titania

Abstract: Titanium dioxide (TiO 2 ) has a number of uses in catalysis, photochemistry, and sensing that are linked to the reducibility of the oxide. Usually, bridging oxygen (O br ) vacancies are assumed to cause the Ti 3d defect state in the band gap of rutile TiO 2 (110). From high-resolution scanning tunneling microscopy and photoelectron spectroscopy measurements, we propose that Ti interstitials in the near-surface regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

111
1,188
5
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 831 publications
(1,323 citation statements)
references
References 46 publications
111
1,188
5
3
Order By: Relevance
“…The fundamental approach to insert charge centers into a material is doping, and the underlying concepts have been introduced and brought to perfection already in the mature field of semiconductor technology. Oxides are subject to self-doping either by native defects or by unwanted impurities, the concentration of which is difficult to control experimentally [63]. Both lattice defects and impurity ions may adopt different charge states in the oxide lattice [64, Fig.…”
Section: Example #2: Nanoparticles and The Metal Oxide Interfacementioning
confidence: 99%
“…The fundamental approach to insert charge centers into a material is doping, and the underlying concepts have been introduced and brought to perfection already in the mature field of semiconductor technology. Oxides are subject to self-doping either by native defects or by unwanted impurities, the concentration of which is difficult to control experimentally [63]. Both lattice defects and impurity ions may adopt different charge states in the oxide lattice [64, Fig.…”
Section: Example #2: Nanoparticles and The Metal Oxide Interfacementioning
confidence: 99%
“…13−15 An alternative picture on the origin of these defect states has been proposed by Wendt and co-workers. 16 Their experimental results indicated that the intensity of band gap states maintains 70% of its original value when the O br H groups are fully consumed on a hydroxylated TiO 2 (110) surface. Based on these findings and accompanying DFT calculations, they proposed that subsurface Ti int is the main origin of the band gap states.…”
mentioning
confidence: 99%
“…Theoretical calculations have also shown that both O br vacancies and Ti int can generate band gap states, although the specific position is very sensitive to the methods used. 15,16,18,19 Technologically, the creation of O br vacancies involves the usage of energetic charged particle bombardment and UHV annealing. These processes might introduce subsurface defects which are difficult to quantitatively assessed, thus it becomes complicated to disentangle various contributions to the band gap states of TiO 2 (110).…”
mentioning
confidence: 99%
“…11,12 The observations showed that the rutile ͑110͒ surface grows by combination of gas-phase oxygen with mobile interstitial Ti 3+ ions from the bulk. The diffusion and reaction of titanium interstitials with adsorbed oxygen have been examined theoretically, 13 and it was found that the energy barriers for Ti interstitial diffusion and reaction were 0.75 and 1.2 eV, respectively. It is our goal to examine theoretically the detailed growth mechanism of the rutile ͑110͒ surface, and in this report on the process we present a systematic examination of various small cluster transition barriers upon the rutile ͑110͒ surface and within the first subsurface layer.…”
Section: Introductionmentioning
confidence: 99%